Pengaruh Tunjangan Kinerja Terhadap Peningkatan Kinerja di Mediasi Gaya Kepemimpinan Transformasional Pada Tenaga Pendidik Di Madrasah Aliyah Negeri Kota Ternate - Muhammad Thahrim; Rusdar rusdar (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine (1) the effect of performance rewards on increasing performance, (2) the effect of performance allowances on transformational leadership styles, (3) the effect of transformational leadership styles on increasing performance, (4) the effect of performance rewards on increasing performance through transformational leadership styles as a mediating variable for educators at Madrasah Aliyah Negeri Ternate City. The sampling technique in this study used the purposive sampling method, namely sampling on the basis of the criteria for teachers with status and receiving performance allowances in accordance with established regulations from the Ministry of Religion. With a sample of 43 people. The results of the study found that (1) performance allowances had a significant positive effect on improving performance in Madrasah Aliyah Negeri Ternate City educators, (2) performance allowances had a significant positive effect on transformational leadership style on Madrasah Aliyah Negeri City Ternate educators, (3) transformational leadership style had an effect significant positive effect on performance improvement in Madrasah Aliyah Negeri educators in Ternate City, (4) indirectly performance allowances have a significant positive effect on performance improvement through transformational leadership style